The Implementation of Solar Power Plant in Catfish Farmer Community at Kampung Lewihalu, Tigaraksa, Tangerang - Supriadi, Oky; Astuti, Fifit; Rohmat, Nur (Pascasarjana Universitas Mataram, 2024)
Based on information provided by the Head of the Catfish Farming Village. The problem encountered in catfish farming villages during the breeding process after catfish farming is that many catfish seeds are eaten by bird pests at night, especially giant shrimp bird pests. According to the partners, the reduction could be up to 50-65% of the total amount of seeds added to the rearing pond. During a nighttime on-site investigation, it was discovered that the catfish pond area was not lit. Therefore, in this charitable activity, we try to provide a lighting solution for catfish ponds and repel kingfisher pests by using environmentally friendly energy, green energy, especially through the use of solar panels. The hope is to be able to reduce bird pests and not burden the partners with monthly electricity bills. From the results obtained in the field, it is known that the result the absence of lighting in the catfish pond area makes king prawn pests eat more catfish seeds than if lighting was provided using flicker flame LED lights and the installation of an off grid solar PV system was not burdensome catfish farmers regarding electricity bills used for lighting.